1992
DOI: 10.1021/ac00044a013
|View full text |Cite
|
Sign up to set email alerts
|

Steady-state voltammetry of strong and weak acids with and without supporting electrolyte

Abstract: Voltammetric reduction of perchloric, phosphork, acetk, and ascorbic acid was investigated under steady-state comlitknr at platinum-and goiddlrk microelectrodes. The ckp.nd.nco of the wave height of proton in perchloric acid on the concentratlon of supporting electrolyte (lithium perchlorate) was compared with the theory for current8 1lmIt.d by migration and dMurlon. The wave height depend8 linearly on hydrog.n ion concentration wlthout and with wpportlng electrolyte up to 0.04 and 0.08 M, respectively. A b , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 6 publications
6
69
0
1
Order By: Relevance
“…Both approaches showed a linear relationship between current density and phosphate concentration. This linear dependency has already been observed by other authors in the steady state limiting reduction current with other weak acids such as acetic, ascorbic, monochloroacetic, lactic and HSO À 4 [43][44][45]. Nevertheless, the dependency between current density and weak acid concentration has not always been found to be linear [34,35] because higher acid concentration induced a higher free proton concentration (reaction (8)) and, following Eq.…”
Section: Voltammetric Studymentioning
confidence: 59%
See 1 more Smart Citation
“…Both approaches showed a linear relationship between current density and phosphate concentration. This linear dependency has already been observed by other authors in the steady state limiting reduction current with other weak acids such as acetic, ascorbic, monochloroacetic, lactic and HSO À 4 [43][44][45]. Nevertheless, the dependency between current density and weak acid concentration has not always been found to be linear [34,35] because higher acid concentration induced a higher free proton concentration (reaction (8)) and, following Eq.…”
Section: Voltammetric Studymentioning
confidence: 59%
“…The electrochemical reduction of phosphates and other weak acids on various electrodes has been the subject of several investigations [29,[34][35][36][37][38][39][40][41][42][43][44][45]. The most widely accepted mechanism for the reduction of weak acids is of the CE (chemical-electrochemical) type, where the dissociation of the acid takes place before the electrochemical reduction of free protons [32][33][34]:…”
Section: Weak Acid Reduction Mechanismsmentioning
confidence: 99%
“…As already noted, weak acids often dissociate before reduction. This process has been documented on platinum disk microelectrodes, 34,35 suggesting that proton reduction from hydronium is the likely process in either direct hydronium or PyrH + reduction cases. Using the relationship in Equation 4 and approximating hydronium and PyrH + reduction as reversible over the scan rates chosen so that the formal potential, E H A/H 2 0 ∼ = E 1/2 , the E 1/2 values calculated for hydronium and PyrH + protons are estimated to be −0.42 V vs. SCE and −0.55 V vs. SCE, close to that observed experimentally.…”
mentioning
confidence: 78%
“…Moreover, the analytical importance of monitoring the acid concentration by voltammetry or amperometry instead of potentiometry has been emphasized [1, 2, 10 -12, 16 -19]. It has been found that strong acids, which are completely dissociated, provided a well defined wave due to the reduction of hydrogen ions [1,2,6,8,14] …”
Section: Introductionmentioning
confidence: 99%